Productive Disruptions: Rethinking the Role of Off-Task Interactions in Collaborative Mathematics Learning - Jennifer M. Langer-Osuna (MDPI AG, 2018)
This paper confronts the myth that all off-task interactions in mathematics classrooms is detrimental to learning. To do so, this paper first explores links between participation, learning, and identity in mathematics education research that points to the importance of positional resources. Positional resources are related to identity processes and carry central functions that regulate learning and doing mathematics together. The paper then frames off-task behavior as an important positional resource in collaborative mathematics learning environments. With these ideas in mind, the paper then closes with new questions for research.